2010
DOI: 10.1002/ceat.201000120
|View full text |Cite
|
Sign up to set email alerts
|

Heat Pipe‐Cooled Microstructured Reactor Concept for Highly Exothermal Ionic Liquid Syntheses

Abstract: Heat pipes used for cooling of microstructured reactors are a new approach for sustainable processing also in the lab-scale within a temperature range from ambient to more than 180°C. The main advantage of heat pipe cooling is the dynamic behavior, i.e., the cooling rate depends on the heat released. Heat pipes can also suppress thermal runaways due to their extremely short response times on momentary temperature rises. As an example, the highly exothermal synthesis of 1-ethyl-3-methylimidazolium trifluorometh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…Continuous micro-reactors can minimise waste generation and can have very high mass and heat transfer rates due to their compact designs [54]. However, one of the challenges of microreactors is multiphase processing.…”
Section: Solids Suspensionmentioning
confidence: 99%
See 1 more Smart Citation
“…Continuous micro-reactors can minimise waste generation and can have very high mass and heat transfer rates due to their compact designs [54]. However, one of the challenges of microreactors is multiphase processing.…”
Section: Solids Suspensionmentioning
confidence: 99%
“…Using the heat pipe system, good thermal control was reported with a total flow rate up to 9.7 mL/min with no fan assistance, and 20 mL/min with fan-assisted forced convection cooling, demonstrating that safe operation of highly exothermic reactions under continuous conditions is possible. Since then, Löwe et al (2010) [54] have commented that the very fast thermal response times and passive heat transfer of the heat pipe can suppress thermal runaways, as any heat transfer fluctuations can be removed at a maximum velocity corresponding to sonic conditions, or a Mach number of 1 for the working fluid. Ehm and Löwe (2011) [77] also used the same heat pipe micro-reactor for ionic liquid synthesis.…”
Section: Rapid Temperature Management and Isothermalisationmentioning
confidence: 99%
“…in the synthesis of 1‐ethyl‐3‐methylimidazolium trifluoromethane sulfonate (Scheme ) 58. 59 With this reactor setup, the cooling rate could be automatically adjusted, depending on the released heat, thereby avoiding the formation of hot spots and thermal runaways. Production rates of 1.24 kg h −1 of the ionic liquid were feasible with this device; this corresponds to a space–time yield of 4270 tonne h −1 m −3 .…”
Section: Making Use Of the “Forbidden”—ex‐regime/high Safety Procementioning
confidence: 99%
“…Hence, a production rate up to 1.24 kg h −1 of 1-ethyl-3-methylimidazolium trifluoromethanesulfonate ([EMIM][OTf ]) can be achieved. 19,20 In a similar way, Waterkamp et al have reported an approach to intensify the synthesis of 1-butyl-3-methylimidazolium bromide ([BMIM]-[Br]) by using a continuously operating micro-reactor system. 21 The reactor set-up consists of a microstructured mixer of 450 µm channel width and a tubular reactor (inner diameter from 2 to 6 mm).…”
Section: Isabel Burguetementioning
confidence: 99%